Sustainability of the rubberwood sector in Malaysia. - Ratnasingam, Jegatheswaran; Ioras, Florin; Wenming, Lu (2011)
Hevea brasiliensis (popularly known as rubber tree) was introduced to Malaya almost a century ago. The wood from the tree has been traditionally regarded as a waste, but since the 1980s' it has found widespread utilization in the wood industry. The total export value of rubberwood products had grown by 39.44% in 2009 compared to 2000 [Malaysian Ringgit (RM) 5100.4 million]. However, the Malaysian export of rubberwood sawn timber declined since 1990, after the imposition of sawn timber export levy. On the other hand, the biggest export proportion of rubberwood products is represented by furniture. Rubberwood furniture accounted for 80% of the total export value of wooden furniture. Meanwhile, the contribution of panel products, such as MDF and particleboard is also substantial. Rubberwood is referred as an environmental friendly material with a low price, but issues related to its sustainable supply are becoming a major concern nowadays. The total area of rubber plantation has been steadily declining over the years as planters claimed less profit and shifted to oil palm cultivation. In this context, unless the profitability of rubber growers is ensured by increasing the net value of the wood resource, the future sustainability of rubberwood in Malaysia will remain debatable.